2017
DOI: 10.1021/acs.jpca.7b10872
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Tautomers of Protonated Aniline Using Differential Mobility Spectrometry and Mass Spectrometry

Abstract: The site of protonation for gas-phase aniline has been debated for many years, with many research groups contributing experimental and computational evidence for either the amino-protonated or the para-carbon-protonated tautomer as the gas-phase global minimum structure. Here, we employ differential mobility spectrometry (DMS) and mass spectrometry (MS) to separate and characterize the amino-protonated (N-protonated) and para-carbon-protonated ( p-protonated) tautomers of aniline. We demonstrate that upon elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…In fact, Lapthorn et al 31 and Wang et al 32 have reported that spectral profiles do change when structural changes happen in precursor ions due to changes in source conditions. 15,32 For example, Walker et al 33 recently published a fragmentation spectrum of protonated aniline that is significantly different from those reported previously. 17,34 In the current study, we have shown that quantitative differences in peak intensity ratios occur when different prototropic tautomers are formed due to changes in humidity in ambient-pressure ion sources.…”
Section: Discussionmentioning
confidence: 80%
“…In fact, Lapthorn et al 31 and Wang et al 32 have reported that spectral profiles do change when structural changes happen in precursor ions due to changes in source conditions. 15,32 For example, Walker et al 33 recently published a fragmentation spectrum of protonated aniline that is significantly different from those reported previously. 17,34 In the current study, we have shown that quantitative differences in peak intensity ratios occur when different prototropic tautomers are formed due to changes in humidity in ambient-pressure ion sources.…”
Section: Discussionmentioning
confidence: 80%
“…Not only are protomers isomers-and therefore unable to be mass-resolved by mass spectrometry-changes in ESI conditions are observed to affect relative protomer populations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This can be an analytical problem when protomers dissociate to different product ions under activation, a phenomenon that can confound assignment by comparison to reference spectra. Differences in the photodissociation of protomers have been used to assign protomer populations, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] although it is difficult to predict how the electronic spectroscopy and photodissociation will be affected by differences in protonation site.…”
Section: Introductionmentioning
confidence: 99%
“…FAIMS has proven to be a powerful tool for separating and analysing protomer populations at atmospheric pressure prior to detection by mass spectrometry. 1,4,6,8,46 Relative-energy calculations are typically coupled with FAIMS analysis to rationalise experimental results. However, it has been shown that theoretical results cannot reliably predict the relative protomer populations generated by ESI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sites of gas‐phase protonation (or deprotonation) of molecules have been the subject of many investigations . Even molecules as simple as carbon monoxide are known to protonate in different ways .…”
Section: Introductionmentioning
confidence: 99%